2020
DOI: 10.1371/journal.pone.0228748
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapists’ perspectives on collaboration and stepped care in outpatient psychotherapy—A qualitative study

Abstract: Objective Stepped and collaborative care with outpatient psychotherapy as one treatment step is guideline-recommended for mental health care. To date, the experiences and evaluation of psychotherapists regarding collaboration and stepped care have been neglected. In order to improve collaborative mental health care, this qualitative study aimed at identifying psychotherapists' perspectives and needs within collaboration and stepped care. Methods Semi-structured qualitative interviews with 20 German outpatient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…Nearly one-fourth of the respondents did not have a modality preference, and the remaining sample preferred self-guided care or group care, revealing substantial variability in care modality preferences for this population of digital mental health care seekers. Given that mental health providers have expressed concern that stepped care prioritizes economic benefits and discounts patient preferences [ 19 ], our study substantiates that stepped care may not only be a more scalable and equitable approach to mental health care, but it also has a more patient-centered model.…”
Section: Discussionsupporting
confidence: 65%
“…Nearly one-fourth of the respondents did not have a modality preference, and the remaining sample preferred self-guided care or group care, revealing substantial variability in care modality preferences for this population of digital mental health care seekers. Given that mental health providers have expressed concern that stepped care prioritizes economic benefits and discounts patient preferences [ 19 ], our study substantiates that stepped care may not only be a more scalable and equitable approach to mental health care, but it also has a more patient-centered model.…”
Section: Discussionsupporting
confidence: 65%
“…Prior research has focused on the perception of collaboration between them and found that PTs considered GPs to be their most important collaboration partners and that collaboration intensity varied from rarely to regularly, with most PTs in favor of more collaboration. A higher intensity of collaboration was linked to small local networks built over time [28]. A recent qualitative study in Norway tested a model for collaborative care.…”
Section: Discussionmentioning
confidence: 99%
“…These cultural differences and divergences in interests between the professional groups, also described as “territoriality” [ 36 ], were equally cited as counterproductive in studies realized in other countries [ 20 , 38 ]. In previous research and in COMET [ 20 , 39 ], both PCPs and MHPs worried about their autonomy and status. At the same time, in COMET and in other studies, MHPs have been identified as the professional group more likely to be subdued when care is advancing towards integrated care, as this is mostly realized within the medical system [ 40 ].…”
Section: Discussionmentioning
confidence: 99%